Between industry and establishment: recent developments in German collective bargaining and codetermination. (3rd July 2021) - Haipeter, Thomas
ABSTRACT: The German dual system of labour relations is at a crossroads. The two cornerstones of the system, collective bargaining at the industry level and codetermination of works councils in companies and establishments, are eroding. Only one third of the workforce is now covered by both institutions. In this situation, trade unions have developed new strategies for revitalisation, including new strategies regarding derogations from collective bargaining agreements, new approaches to organising, and new projects to activate works councils. As a result, the traditional boundaries between union action at the establishment and industry levels, traditionally characterised by a strict separation of roles between works councils and trade unions, are dissolving. The trade unions are now developing active strategies at the establishment level with the aim of strengthening their position in the companies, and strengthening the capacity of works councils to act. At the same time, the importance of works councils as actors in collective bargaining is increasing. This new interplay of actors and levels seems to be an important precondition for the revitalisation of German industrial relations, even if it does not mean that all problems will be solved.